IMPROVEMENT OF MARKETING STRATEGY WITH TRAINING OF GAYO ARABICA COFFEE PROMOTION VIDEO DESIGN - Fadli, Fadli; Suryadi, Suryadi; Tambarta, Emmia; Sinta, Irada (RADJA PUBLIKA, 2022)
The pandemic of Corona Virus Disease (COVID-19) has been giving a considerable impact on various sectors in Indonesia, especially in the trade sector. The corona epidemic which has become increasing massive lately has ultimately disrupted the marketing process to a significant point. World Trade is currently facing a big challenge, namely economic recession for almost all countries in the world. To deal with this problem, Indonesia must be able to design a strategy so that it can survive the threat of an economic recession. The solution that can be implemented is to increase export potential for superior commodities. One of the export commodities that will be able to maintain Indonesia's economic position is Gayo Arabica coffee. Gayo coffee is one of the most popular types of Arabica coffee in the international market. This opportunity can be the main basis for avoiding economic recession conditions. Gayo coffee has been recognized as one of the best coffee beans in the world. During The pandemic of COVID-19, hygiene was the most important issue in all process. Many kinds of perspectives about the processing of Gayo Arabica coffee are considered not qualified with international quality in terms of hygiene / food safety which can be the main obstacles in the process of the Gayo Arabica coffee trade itself. Promotion strategy is one of the best solutions in dealing with these food safety issues. The promotional strategy is directed at designing a promotional video that explains how the Gayo Arabica coffee processing heppens in accordance with the health protocol during the COVID-19 pandemic. This activity can improve the marketing strategy with training on the design of the Gayo Arabica coffee promotion video which aims to: provide knowledge about the design of the Gayo Arabica coffee promotion video, to become a forum for training the skills of young farmers in product marketing strategies, as a reference for the next community service activities. Activities were carried out in Central Aceh District from July to December.